1335. Safety and Pharmacokinetic Profile of PC786, a Novel Inhibitor of Respiratory Syncytial Virus L-protein Polymerase, in a Single and Multiple-Ascending Dose Study in Healthy Volunteer and Mild Asthmatics. (26th November 2018) - Cass, Lindsey; Davis, Amanda; Murray, Alison; Woodward, Kathy; Ito, Kazuhiro; Strong, Pete; Rapeport, Garth
Abstract: Background: RSV is the most common cause of bronchiolitis in infants and is responsible for severe respiratory infections in the elderly and immunocompromised populations. RSV replicates in the columnar epithelial cells of the proximal and distal airways which are accessible to inhaled therapies. PC786 is a potent non-nucleoside RSV L-protein polymerase inhibitor designed for inhaled delivery. In preclinical studies, PC786 exhibits prolonged lung tissue residence with minimal systemic exposure, thus limiting the potential for adverse systemic effects. Methods: A phase 1 study was conducted to evaluate the safety and pharmacokinetics of PC786 delivered in a suspension formulation by nebulizer (PARI LC SPRINT ® device). Healthy volunteers (HVs) received placebo or PC786 as single ascending doses (0.5–20 mg, Cohort (C) 1), 5 mg BD for 7 days (C2), or 10 mg BD for 7 days (C3). Mild asthmatics received a single dose of PC786 5 mg or placebo (C4). PC786 PK was measured in plasma and in nasal mucosal lining fluid (MLF) collected using a synthetic absorptive matrix. Results: PC786 was well tolerated, with no significant adverse clinical nor laboratory findings. Following single inhaled doses PC786 appeared rapidly in the plasma; mean plasma C max of 190, 571, 1, 760, and 3, 270 pg/mL, for the 0.5, 2, 8, and 20 mg doses, respectively, were measured on average at 0.68 to 0.93 hours ( T max ) post-inhalation. Following administration of 5 mg BD (C2) the extent of accumulation was approximately 2-fold. The geometric mean apparent terminal half-life measured following 10 mg BD (C3) was 97 hours. The ratio of MLF:plasma concentrations ranged from 6, 347 (+2 hours) to 1, 050 (+24h). Conclusion: PC786 was well tolerated by HVs and asthmatics. The compound showed a rapid Tmax, suggesting rapid exposure of the respiratory epithelium. The PC786 concentrations in MLF exceed the IC90 for RSV, but circulating plasma concentrations were low. The MLF:plasma measured in this study was consistent with lung:plasma ratios measured in preclinical studies. The long plasma half-life is consistent with slow absorption from the lung being the dominant process controlling systemic kinetic behavior. The long t½ and 2-fold accumulation ratio observed on repeat dosing supports once daily dosing in subsequent studies. Disclosures: L. Cass, Pulmocide Ltd.: Employee and Shareholder, Salary. A. Davis, Pulmocide Ltd.: Employee and Shareholder, Salary. A. Murray, Pulmocide Ltd.: Employee and Shareholder, Salary. K. Woodward, Pulmocide Ltd.: Consultant, Consulting fee. K. Ito, Pulmocide Ltd.: Employee and Shareholder, Salary. P. Strong, Pulmocide Ltd.: Board Member, Employee and Shareholder, Salary. G. Rapeport, Pulmocide Ltd.: Board Member, Employee and Shareholder, Salary.